Hydrogen storage potential of coal: influence of coal on pore structure and adsorption mechanisms - Tao, Liru; Ju, Yiwen (Frontiers in Earth Science, 2025)
The development of clean energy is crucial for the transition to a low-carbon economy, and hydrogen, with its high energy density and environmental friendliness, has become increasingly important. Coal, as a porous medium, provides a possible site for underground storage of hydrogen. The structural evolution of coal during coalification significantly influences hydrogen adsorption capabilities within nanopores, yet comprehensive studies evaluating the hydrogen adsorption and storage potential in coals of different ranks (low, medium, and high) remain limited. Our study innovatively addresses this research gap by investigating the hydrogen storage potential in low-, medium-, and high-rank coal seams, focusing particularly on how molecular structure affects pore structure and hydrogen adsorption mechanisms. Coal samples representing various coal ranks were collected from different basins in China. Multiple experimental techniques, including CO2 and low-temperature N2 adsorption, hydrogen adsorption isotherms, XRD, and HRTEM analyses, were employed to characterize coal structures and hydrogen adsorption properties comprehensively. Results indicate that coal is rich in nanopores. The evolution of coal molecular structure during coalification has a correlation with the microporous evolution characteristics, which determines the hydrogen adsorption capacity. With the increase of coal rank, the hydrogen adsorption capacity showed an obvious four-stage evolution pattern. High-rank coal with strong hydrogen adsorption capacity, faster adsorption rate and lower hydrogen retention after desorption, and is more suitable for underground hydrogen storage. These findings enhance the fundamental understanding of coal-hydrogen interactions and provide crucial guidelines for selecting optimal geological reservoirs for underground hydrogen storage.